2016
DOI: 10.1007/s00701-016-2994-y
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia due to venous neurovascular conflicts: outcome after microvascular decompression in a series of 55 consecutive patients

Abstract: Venous NVC as a cause of TN is far from rare. MVD with complete liberation of the entire root in cases with clear-cut venous compression on imaging studies gives a good probability of long-term pain relief, thus encouraging to propose surgery for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…4,8,10,15,17 The surgical outcome was good or excellent in 70.6%-100% of these patients, 4,8,10,11,15 and recurrence was observed in 0%-36.4% of them. 4,8,10,14 Compared to those with arterial compression, the patients with venous compression may have relatively less pain improvement and higher recurrence rates, although some have reported excellent outcomes in those with venous compression. 10 Venous compression is more frequently seen in patients with atypical (type 2) neuralgia than in those with typical (type 1) disease, 17 and surgical outcomes of patients with atypical disease are inferior to those of patients with typical neuralgia.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…4,8,10,15,17 The surgical outcome was good or excellent in 70.6%-100% of these patients, 4,8,10,11,15 and recurrence was observed in 0%-36.4% of them. 4,8,10,14 Compared to those with arterial compression, the patients with venous compression may have relatively less pain improvement and higher recurrence rates, although some have reported excellent outcomes in those with venous compression. 10 Venous compression is more frequently seen in patients with atypical (type 2) neuralgia than in those with typical (type 1) disease, 17 and surgical outcomes of patients with atypical disease are inferior to those of patients with typical neuralgia.…”
Section: Discussionmentioning
confidence: 91%
“…Although preserving the venous system may make the surgery slightly more complex, Dumot et al have reported a similar surgical strategy with excellent surgical results. 4 We can perform wide and complete surgical manipulations of the offending vessels, using multiple surgical corridors, and preserve the venous flow of the cerebellum and brainstem (Fig. 1H, Video 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations